2010
DOI: 10.1007/s00464-010-1194-8
|View full text |Cite
|
Sign up to set email alerts
|

Newly designed large cell Niti-S stent for malignant hilar biliary obstruction: a pilot study

Abstract: The newly designed endoscopic metallic stent may be feasible and effective for malignant hilar biliary obstruction, and endoscopic reintervention is relatively simple.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 18 publications
3
73
1
Order By: Relevance
“…We investigated papers about hilar obstruction due to malignant biliary stricture including HCC and cholangiocarcinoma (table 1) [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24]. The successful drainage rate ranges from 72 to 100%.…”
Section: Drainagementioning
confidence: 99%
“…We investigated papers about hilar obstruction due to malignant biliary stricture including HCC and cholangiocarcinoma (table 1) [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24]. The successful drainage rate ranges from 72 to 100%.…”
Section: Drainagementioning
confidence: 99%
“…Bilateral SEMS stenting can be performed using the SIS or SBS technique. In the SIS technique, the second SEMS is inserted to the contralateral hepatic duct through the mesh of the first SEMS [16][17][18][19][20][21][22]. Conversely, in the SBS technique, two SEMSs are inserted parallel to each other into the right and left hepatic duct [23][24][25][26] (Fig.…”
Section: Multiple Stenting Methods (Stent-in-stent or Side-by-side)mentioning
confidence: 99%
“…To overcome this hurdle, a large open-cell wire mesh SEMS (Niti-S large cell D-type; Taewoong Corp., Seoul, Korea) was developed. Kogure et al [20] demonstrated high technical success rates with large-cell SEMSs in the bilateral SIS technique. A newly designed, closed-cell and cross-wire stent is another SEMS (Bonastent M-Hilar; Standard Sci Tech Inc., Seoul, Korea) dedicated to SIS stenting, which comprises a hook and cross-wired structure on the proximal and distal portions, and only the cross-wired structure on the central portion facilitates the SIS technique [17].…”
Section: Progress Of Sems For Bilateral Stentingmentioning
confidence: 99%
“…Median stent patency was 202 days. 69 Although the results were comparable with unilateral and bilateral side-by-side stent placement, Kogure and others have demonstrated good success with the stent-in-stent method.…”
mentioning
confidence: 85%
“…Kogure et al examined the feasibility and efficacy of this large mesh stent for both unilateral and bilateral drainage of malignant hilar biliary obstruction. 69 Twelve patients first underwent unilateral or bilateral drainage using a plastic stent or nasobiliary drainage tube. If jaundice improved, the plastic stent or drainage tube was replaced with a unilateral large mesh biliary stent; and if jaundice did not improve, bilateral large mesh stents were placed.…”
mentioning
confidence: 99%